Herpetology Collection NRM - Sven Kullander (Swedish Museum of Natural History, 2010)
This database contains information on the so far registered specimens in the Herpetology Collection of the Swedish Museum of Natural History. The database is managed with The Artedian collection management system in MS-Access. The main tables describe collecting events and collection objects which are related on a one to many relationships. The database is Darwin Core compatible but uses alternative table names and includes also loan routines, document management and other components of collection management. Principal items managed are objects (catalog number, identification, number of specimens, sex size, location in collection, collection space, preservative, identifier, etc.); localities (collecting events with date, collector, geographic information including co-ordinates, and more), collecting site habitat; loans (with extensive metadata), accession information (date of accession, donors, acquisition conditions etc., specimen preservation progress). DNA samples are managed as subsamples of objects. Specimen and collecting site images are managed with extensive metadata. The database has a web presentation at http://artedi.nrm.se/nrmfish.
Keywords: Occurrence; Specimen; Occurrence; OCCURRENCE; Biological Sciences; Biologi